P1-S6.21 Chlamydia trachomatis screening initiative among female US army soldiers deployed to Korea. (10th July 2011) - Jordan, N; Clemmons, N; Gaydos, J; Fishman, J; Jacobsmuhlen, T; Lee, H Choon; Meyers, M; Klein, T
Abstract : Objectives: To determine the prevalence of Chlamydia trachomatis (Ct) infections among female US Army soldiers deployed to the Republic of Korea; to identify high-risk groups; and to develop data to inform Army leaders and public health decision makers regarding the program's impact. Methods: All females reporting (in-processing) to the Eighth US Army, Republic of Korea, between 1 November 2007 and 31 December 2009 received an educational STI brief and a questionnaire, and were requested to provide a urine sample for Ct and gonorrhoea testing using the Aptima Combo 2 Assay. Contact tracing was conducted for all identified cases. Descriptive analyses of the population of interest and data collected during calendar years 2008–2009 were performed. A logistic regression model was generated to identify statistically significant risk factors. Results: Women deployed to Korea differed somewhat demographically when compared to the overall female Army population; a higher proportion of known high risk groups was observed (eg, women under 25 years of age). A total of 3761 women were screened during the 2 calendar years, with an overall positive rate of 5.7%. Ct rates were as high as 11.4% among women under 20 years, and decreased with increasing age. Rates varied considerably by race, with the highest rates observed among American Indians/Alaskan natives (9.3%), followed by Black females (6.5%). The Eighth US Army screening program was associated with diagnosis of infections at an earlier age (22.1 years on average during the screening program, as compared to 26.1 years on average before the program was initiated). Statistically significant differences were observed, with higher rates found among Black women and women <25 years of age. Conclusion: A high prevalence of infection was observed, highlighting the need for a continued Eighth US Army screening program. Furthermore, the program demonstrated that universal screening during Army in-processing was feasible and resulted in detection of Ct at earlier ages, which likely reduces disease transmission, medical complications, and associated costs with treatment. These findings have implications not only for the continuation of the program in the Republic of Korea, but also for the expansion of such programs during in-processing activities among other military high risk populations (eg, Army recruits).